The Virtues of Justice: Toward a Moral and Jurisprudential Psychology. (July 2022) - Williams, Christopher; Arrigo, Bruce
Within the theoretical literature on crime control and offender therapy, little has been written about the importance of virtue ethics in the experience of human justice and in the evolution of the common good. As a theory of being, the aretaic tradition extols eudemonic existence (i.e., excellence, flourishing) as a relational habit of developing character that is both practiced and embodied over time. What this implies is that virtue justice depends on a set of assumptions and predispositions—both moral and jurisprudential—whose meanings are essential to comprehending its psychological structure. This article sets out to explore several themes that our integral to our thesis on the virtues (i.e., the being) of justice. We reclaim justice's aretaic significance, critique the common conflation of justice and law, discuss how the dominant legalistic conception of justice is rooted in a particular view of human nature, suggest how justice might be more properly grounded in natural moral sensibilities, and provide a tentative explication of the psychological character of justice as a twofold moral disposition. Given this exploratory commentary, we conclude by reflecting on how individual well-being, system-wide progress, and transformative social change are both possible and practical, in the interest of promoting the virtues of justice within the practice of crime control and offender therapy.